2020
DOI: 10.1097/pgp.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Microscopic Granulosa Cell Proliferations: Tumorlet or Non-neoplastic?

Abstract: Microscopic granulosa cell proliferations are rare incidental findings in ovarian and extraovarian tissue, and can simulate granulosa cell tumors. We report a case of a 22-yr-old nulliparous woman with incidental microscopic granulosa cell proliferation in the wall of an endometriotic cyst. Excision of the cyst revealed extensive endometriosis and incidental microscopic nests and cords of granulosa cells measuring 1.5 mm and positive for inhibin A and calretinin. A rare Call-Exner body was noted. An extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Molecular analysis was also performed, and the 3 cases lacking FOXL2 mutation were interpreted as non-neoplastic AGCT-like proliferations (13). AGCT-like proliferations have been reported in the walls of large (10-18 cm) endometriotic cysts; when assessed, FOXL2 mutations have not been detected (14,15). The authors consider FOXL2 mutation testing to be useful in confirming a diagnosis of true AGCT.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis was also performed, and the 3 cases lacking FOXL2 mutation were interpreted as non-neoplastic AGCT-like proliferations (13). AGCT-like proliferations have been reported in the walls of large (10-18 cm) endometriotic cysts; when assessed, FOXL2 mutations have not been detected (14,15). The authors consider FOXL2 mutation testing to be useful in confirming a diagnosis of true AGCT.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the incidental finding of isolated microscopic proliferations of granulosa cells, both ovarian and extraovarian, that may mimic an early AGCT or a metastasis (31). These are usually multiple and range in size from <1 mm up to 5 mm.…”
Section: Fig 2 (A and B) Serous Borderline Tumor Component With Papil...mentioning
confidence: 99%